G-function Solutions for Diffusion and Laplace's equations - Pishkoo, Amir; Darus, Maslina (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper the Diffusion equation and Laplace's equation is solved by Modiffied separation of variables (MSV) method, suggested by Pishkoo and Darus . Using this method, Meijer's G-function solutions are derived in cylindrical coordinates system for two typical problems. These complex functions include all elementary functions and most of the special functions which are the solution of extensive problems in Physics and engineering.